Pelestarian Kearifan Lokal Desa Pakraman Tenganan Pegringsingan dalam Pengelolaan Hutan - Saputro, Fajar Bagus Ekanda; Mulyono, Joko (University of Jember, 2015)
Abstract Local wisdom of Pakraman Tenganan Pegringsingan villagers highly contributes to the conservation of forests in the village area. In today’s globalization and modernization era in which the existence of local wisdom is considered to be fading in various community groups, the community local wisdom in the form of awig-awig governing the forest management still exists until now. The consistent existence of local knowledge is closely linked to conservation efforts in order to maintain its existence in community live. This research aimed to describe the preservation of local wisdom in forest management undertaken by community members of Pakraman Pegringsingan Tenganan Village. The explanation of this used a dialectical theory of objective structures and subjective phenomena by Pierre Bourdieu. The research applied qualitative approach, and the informants were determined using purposive sampling. Data collection used observation, interview, and documentation. The research results showed that the efforts of local wisdom preservation in the form of awig-awig that governs the forest management in community of Tenganan Pakraman Pegringsingan village were conducted by documentation, systematization, translation improvement into Indonesian, and socialization of awig-awig. The local wisdom has been a habitus in the local community, in which the habitus is dialectically related to the field that supports the sustainability of local wisdom in the live of people in Pakraman Tenganan Pegringsingan.